(untitled) (Journal of the College of Basic Education, 2022)
The current research deals with the powder method to study a system with a mineral base of copper and the first support material of silicon carbide at a constant rate of 5% while the second support material was a variable from Nano crystalline and with a cementation ratio of (0,5,10,15,20) %. The powders were mixed by the volumetric method. Due to the difference in densities between the three powders, the grinding process was carried out for a two-hour period with a mill of local manufacture and with steel balls. Then, the mixed powders were pressed with a Turkish hydraulic press at a pressure of (5 tons) and for one minute. The prepared samples were thermally sintered in an English furnace at 900 °C for only two hours. Moreover, various tests were performed on the models including (hardness, density, porosity, X-ray diffraction) before and after sintering. The results showed that the best mixing ratio was 15% zirconia, which included micro-hardness (90.81 Hv) and less porosity (14.6%). Also, the density at 15% was (7.897 g/cm3). X-ray diffraction showed that the materials used were the base material (copper) with a cubic phase (crystalline) at Miller’s coefficients (111), (200) and (220), as well as silicon carbide (SiC) with the fixed support material and a cubic structure. The emergence of the variable reinforced zirconia Nano composite (ZrO2), Miller’s coefficients (111), (200), (220), (311) and (222), and the monoclinic composition of Miller’s coefficients (011), (110), (1-11), (111), (002), (102-), (112), (013).